2010
DOI: 10.1128/aem.03003-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic and Phenotypic Analysis of the Responses ofBacillus cereusto Various Disinfectant Treatments

Abstract: Antimicrobial chemicals are widely applied to clean and disinfect food-contacting surfaces. However, the cellular response of bacteria to various disinfectants is unclear. In this study, the physiological and genome-wide transcriptional responses of Bacillus cereus ATCC 14579 exposed to four different disinfectants (benzalkonium chloride, sodium hypochlorite, hydrogen peroxide, and peracetic acid) were analyzed. For each disinfectant, concentrations leading to the attenuation of growth, growth arrest, and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 64 publications
6
78
0
Order By: Relevance
“…In previous studies, UV was shown to induce the expression of SOS response genes in E. coli, which is consistent with DNA damage (33,57). Furthermore, exposure to PAA reduced the expression of membrane proteins but increased the expression of chaperone proteins, of oxidative stress response genes, and of sulfur-containing amino acid metabolism genes in different species (58)(59)(60)(61). All these effects are consistent with the oxidative reaction with proteins as the chemical diffuses into the cell.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In previous studies, UV was shown to induce the expression of SOS response genes in E. coli, which is consistent with DNA damage (33,57). Furthermore, exposure to PAA reduced the expression of membrane proteins but increased the expression of chaperone proteins, of oxidative stress response genes, and of sulfur-containing amino acid metabolism genes in different species (58)(59)(60)(61). All these effects are consistent with the oxidative reaction with proteins as the chemical diffuses into the cell.…”
Section: Discussionsupporting
confidence: 78%
“…Demple and Halbrook (62) reported that hydrogen peroxide induced DNA damage repair systems in E. coli. In another study with Bacillus cereus, PAA and hydrogen peroxide have been found to induce DNA damage repair systems and SOS response genes, but quaternary ammonium compounds (QAC) or hypochlorous acid did not provoke the same effects (61). Similarly to hydrogen peroxide or PAA, UV irradiation also induces the DNA repair mechanisms in the E. coli cell (63).…”
Section: Discussionmentioning
confidence: 99%
“…Sterol carrier proteins transfer steroids across cellular membranes (37), and enoyl-acyl carrier reductase is involved in the fatty acid elongation cycle (38); thus, both genes modulate membrane fluidity, permeability, and thickness and could play a role in alleviating BAC toxicity by enhancing cell membrane integrity. Cell membrane biosynthesis represents an important cellular response to BACs, which are membrane disruption agents (39,40). Hence, the genes identified here might contribute to the fitness advantage of P. nitroreducens related to maintaining cell membrane integrity in the presence of BAC toxicity, although this hypothesis awaits experimental verification.…”
Section: Discussionmentioning
confidence: 88%
“…Peracetic acid (PAA) is a common sanitizer used in the dairy industry (Ceragioli et al, 2010) and is normally used in food industries in Brazil at concentrations of 300 -700 mg/L (Quarentei et al, 2011). PAA has a broad spectrum and is a strong oxidizing agent that is decomposed into safe waste products (Van der Veen, Abee, 2011).…”
Section: Introductionmentioning
confidence: 99%